2021
DOI: 10.1007/s12630-021-02073-4
|View full text |Cite
|
Sign up to set email alerts
|

Provider attitudes and satisfaction with rapid preoperative point-of-care COVID-19 testing using ID NOW™

Abstract: Purpose Healthcare workers have experienced high levels of anxiety during the COVID-19 pandemic, particularly when caring for patients with unknown infection status. We trialled rapid preoperative point-of-care COVID-19 testing using the Abbott ID NOW TM COVID-19 for clinical validation in an urgent surgical population at a single centre in British Columbia, Canada. Here, we sought to determine the opinions and beliefs of operating room (OR) staff on the usefulness and effectiveness of point-of-care tests on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…In the pre-operative setting, POC testing allowed the rescheduling of elective surgeries of asymptomatic patients who test positive for SARS-CoV-2, avoiding the risk of post-surgical morbidity and mortality or potential nosocomial transmissions ( 8 ). POC testing was also shown to increase a sense of workplace safety and improve morale ( 9 ) and was easily incorporated into pre-operative and occupational health decision-making ( 9 11 ). Future studies should consider evaluating the impact of NAAT-RDTs in each setting, comparing individuals who present with and without symptoms, as well as considerations for costs compared to laboratory testing.…”
Section: Discussionmentioning
confidence: 99%
“…In the pre-operative setting, POC testing allowed the rescheduling of elective surgeries of asymptomatic patients who test positive for SARS-CoV-2, avoiding the risk of post-surgical morbidity and mortality or potential nosocomial transmissions ( 8 ). POC testing was also shown to increase a sense of workplace safety and improve morale ( 9 ) and was easily incorporated into pre-operative and occupational health decision-making ( 9 11 ). Future studies should consider evaluating the impact of NAAT-RDTs in each setting, comparing individuals who present with and without symptoms, as well as considerations for costs compared to laboratory testing.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 It has been shown that the use of COVID-19 POCT has positively affected healthcare providers through improved morale, and reduced worry associated with COVID-19 without disruption of workflow. 21 The acceptance of COVID-19 POC tests by both healthcare providers and patients will, optimistically, improve the way that POCT is perceived, and contribute to growing adoption rates. The successful implementation of POC tests proven to be cost-effective demands transformation and integration of services across healthcare organizations.…”
Section: Introductionmentioning
confidence: 99%